Женщины вокруг Наполеона: [перевод] / Г. Кирхейзен - Кирхейзен Гертруда (Лада-Маком, 1993)
Экземпляры: Ф. 4 (20191113) / Инвентарный номер: 47357 / Цена: 10.00 / Сис.шифр: 63.3(4) / Авт.знак: К43 / ГРНТИ: 03 / ББК: 63.3(4Фр)512-8